Performance of waterborne intumescent coating with hybrid industrial and biofillers for steel protection / Khairunisa Md Nasir - Khairunisa , Md Nasir (2021)
In recent decades, the disastrous accidents caused by damaged steel structure in the event of the fire have reminded people of the risk of fire in industrial buildings. The use of intumescent coatings is one of the most efficient methods to protect materials against fire. The coating comprises three active elements bounded together with a binder, which then reacts together at higher temperatures. Under the action of heat, the coating expands and forms a thick porous char layer to insulate the substance, thereby prolonging the building from collapsing under severe fire conditions. Considering ecological issues, the use of waterborne resin as a binder will minimise smoke and toxic fume emission. Meanwhile, the use of synthetic solvent borne resin can have an adverse effect because intumescent coatings contain synthetic polymers which release acidic degradation products and cause water pollution. Selection of a filler to be introduced in flame retardant properties is determined by several factors which include chemical compatibility during the mixture, suitable viscosity and residue left after decomposition thermal analysis. In this research, the single filler system involves industrial fillers commonly used in many industries namely, titanium dioxide (TiO2), aluminium hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2) and calcium carbonate (CaCO3). The search for more environmentally friendly intumescent coatings has led to the utilisation of rice husk ash (RHA) and chicken eggshell (CES) as biofillers hybrid with industrial fillers, TiO2 and Al(OH)3 reinforcing the quality and effectiveness as hybrid fillers system. Incorporating waste biofillers specifically into coatings can greatly minimise cost and reduce the amount of wastes. Both intumescent coating systems were investigated based on three characterisations; (a) physical and chemical properties; (b) fire performances test; (c) mechanical test. The hybrid fillers system was evaluated in extensive fire standard analysis using fire propagation test (BS476: Part 6), surface spread of flame (BS476: Part 7) and cone calorimeter to identify the key combustion properties of coating material properties. The higher charred yields demonstrated by coatings with TiO2 and CaCO3 have led to the lower equilibrium temperature below 300°C, while coating with Al(OH)3 showed an excellent flammability resistance with the highest oxygen index value of 35. Hybrid coating with TiO2/RHA showed satisfactory fire behaviour effect in terms of char expansion rate, lowest total heat release rate and last to ignite, while hybrid coating with TiO2/Al(OH)3/RHA/CES presented the lowest amount of released CO and high CO2 production percentage. This research presents the significant improvement of hybrid fillers system, where all coatings required high oxygen concentration to support the burning process. From the BS 476: Part 7, all coatings were classified as Class 1 (the bestclass) showing least distance of flame spreading and also fulfilled the best Class 0 which limits the amount of heat released in BS 476: Part 6. The originality of this work was emphasized on the intumescent coating with the addition of RHA and CES as biofillers hybrid with industrial fillers. In addition, waterborne resin was used to minimise the volatile organic compound emissions from synthetic solvent-borne binder.